Roger Vailland communiste, ou l’importance d’être constant - Christian Petr (Itinéraires)
As far back as 1926, Roger Vailland expresses the concern of not disuniting revolt and conflict against ethical and aesthetical conformity of the project of world change. His participation in the Resistance movement, his adhesion to the Communist Party in 1952 are, for him, two factors of personal emancipation which reinforce this concern, this desire and this will, which, even beyond his withdrawal, in 1959, from the Communist Party, continue to endure until his death in 1965.